Model Pembelajaran CLIS (Children Learning In Science) dengan Metode Eksperimen terhadap Pengaruh Hasil Belajar IPA di SDN Trimulyo 01 - Septiani Nurjanah; Nur Fajrie; Sri Surachmi W (Departement of Mathematics Education, 2023)
Science Learning in clasc IV at SDN Trimulyo 01 Juwana distric before using the CLIS model, it was found that there were still many students who experienced difficulties. From the daily test results of 25 students, only 9 students (36%) reached the Minimum Completeness Criteria (KKM) target of 70. The aim of this study was to describe the application of the CLIS model with the experimental method in improving science learning outcomes. Classroom action research was carried out in 2 stages, namely cycle I and cycle II. The research results from student formative test data show that the percentage of learning completeness by 36% in the pre-cycle increased to 92% in cycle II and has achieved indicators of success. The conclusion of this study is that the use of the CLIS model with the experimental method can improve student learning outcomes in science subjects.